Design and application of an improved and upgraded version of restraint gloves (一种改良升级版约束手套的设计与应用) - LAI Ziqin (赖紫钦); SUN Xiumei (孙秀梅) (Association of Integrative Nursing, 2024)
Protective restraint is a kind of auxiliary medical measure used by patients in delirium, agitation, and non-cooperation with treatment. Its purpose is to ensure the continuity of treatment and prevent patients from harming themselves. This study introduces the design and use method of a utility model improved and upgraded version of restraint gloves, which can ensure the safety of patients and maximize the comfort of patients. (保护性约束是患者在谵妄、躁动、不配合治疗的情况下使用的一种医疗辅助措施, 其目的是保证治疗的持续性和防止患者对自身的伤害。本研究介绍一款实用新型改良升级版约束手套的设计和使用方法, 在保证患者安全的同时最大限度的提高了患者的舒适度。)